THE INFLUENCE OF LEADERSHIP, MOTIVATION, AND TRAINING ON EMPLOYEE PERFORMANCE OF BADAN KEPEGAWAIAN DAERAH (BKD) KABANJAHE, KAB. KARO - Cut Fitri Rostina; Andrian Felix Gerson Nainggolan; Rotua Chyntia Sembiring (Institute of Computer Science (IOCS), 2022)
Employee performance has an impact on a company's performance. This needs to be improved in the direction of meet the company's objectives. Employee performance can be improved through good leadership, high employee motivation, and employee training. The purpose of this research is to determine the impact of leadership, motivation, and training on employee performance, both individually and collectively. The descriptive and quantitative research methods were used. Observations, and interviews with BKD employees from Karo Regency were used to collect data. The interview technique was carried out in an unstructured manner using questionnaire. Data analysis using Test T and Test F. Analysis results show that leadership has a significant impact on employee performance; work motivation has a significant impact on employee performance; training has an impact on employee performance; and all three together have an impact on employee performance. Variable work discipline as the most dominant variable affecting employee performance.